THE INFLUENCE OF MOTIVATION, EDUCATION LEVEL, AND LEADERSHIP MODEL ON THE PERFORMANCE OF MEMBERS OF DONGGALA DISTRICT REGIONAL PEOPLE’S REPRESENTATIVE COUNCIL - Madurika, Sriyanti; Hasanuddin, Bakri; Syamsuddin, Syamsuddin (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2021)
This research aimed to examine and explain the influence of motivation, education level, and leadership model on the performance of members of Donggala District Regional People’s Representative Council. Type of the research was survey research. The population consisted of 30 members of Donggala District Regional People’s Representative Council. The sample was determined based on the census where the entire population was sampled. Data collection techniques used a questionnaire. The data analysis technique used descriptive and inferential statistics in the form of multiple regression using the SPSS version 25 application. The results show that the motivation and leadership model have a positive and significant influence on the performance of the members of Donggala District Regional People’s Representative Council. The level of education has no significant influence on the performance of members of Donggala District Regional People’s Representative Council. Simultaneously, the three independent variables have a significant positive influence on the performance of the members of Donggala District Regional People’s Representative Council. Keywords: Motivation, Education Level, Leadership Model and Performance